Crossing Style Borders: New Inroads in Training Teachers of Singing. Issue 2 (3rd May 2020) - Bartlett, Irene
ABSTRACT: For teachers of singing, traveling new roads of genre and style can be a fraught journey. While much has been written concerning the differences in voice production parameters for singers of classical and contemporary commercial music (CCM), the lack of effective pedagogy training programs has left many teachers feeling like hitchhikers trying to find their own way as they negotiate an ever changing landscape of music and the myriad of aesthetic elements and effects that define each style. This paper is a discussion of the possibilities for future training of teachers of singing and a report of the success of a master's level pedagogy program where teachers are trained to view voice building as the journey and style as the destination.